Methods for calibration of radiometric receiver for remote diagnostics of animals diseases - Семенец, В.В.; Аврунин, О.Г.; Косулина, Н.Г.; Гуцол, Т.Д.; Ляшенко, Г.А. (Radiotekhnika, 2019)
One of the features of the modern stage of agricultural development in Ukraine is the growth of economic basics and improvement of illogical prerequisites to the level of the needs of industrial animal husbandry, the merger of veterinary and zootechnical sciences and increasing their influence directly on production processes. Based on theoretical and experimental studies, a radiometric system was created for remote measurement of electromagnetic radiation of animal organs with the following parameters: sensitivity 10-15 – 10-17 Wt, frequency range 30 – 40 GHz, speed 2 – 4 s, measurement accuracy 0.1 ° C. A calibration method has been developed to provide the necessary parameters of a radiometric receiver for the diagnosis of animals.